Exploring faculty perspectives toward developing a planetary health curriculum for family medicine residents at the University of Toronto - KitShan Lee; KitShan Lee; Elisabeth-Abigail Ramdawar; Elisabeth-Abigail Ramdawar; Elisabeth-Abigail Ramdawar; Samantha Green; Samantha Green; Rachel Adilman; Rachel Adilman; Azzra Mangalji; Azzra Mangalji (Frontiers in Public Health, 2025)
BackgroundClimate change is the greatest threat to human health of this century, yet limited formal curriculum exists within postgraduate family medicine (FM) programs across Canada. As outlined by The College of Family Physicians of Canada (CFPC) Guides for Improvement of Family Medicine Training (GIFT) report, learners have called for planetary health (including climate change) education and recommended a curriculum framework. This study aimed to understand University of Toronto Department of Family Medicine faculty attitudes around implementing a planetary health curriculum within the FM residency program.MethodsThis study used a qualitative descriptive design. Thirty faculty members from various teaching, curriculum, and leadership positions were invited to participate in virtual semi-structured video interviews. Data was collected and analyzed using thematic analysis.ResultsThirteen interviews were conducted between May–September 2022. Participants perceived planetary health was relevant to FM, but most were unfamiliar with the term. Four overarching themes were developed from the data: (1) curriculum implementation, (2) curriculum development, (3) barriers, and (4) attitudes. Barriers to integrating PH learning objectives include a lack of faculty knowledge and skills, burnout, and an already saturated FM curriculum.ConclusionTo address the climate crisis, there is need for a planetary health curriculum, yet faculty have a limited understanding of this topic. This knowledge gap is one of multiple barriers to curriculum implementation this study identified. This study provides insight and suggestions for tools that may aid planetary health curriculum development and implementation.